Scrub typhus serologic testing with the indirect immunofluorescence method as a diagnostic gold standard: a lack of consensus leads to a lot of confusion. - Blacksell, S; Bryant, N; Paris, D; Doust, J; Sakoda, Y; Day, N (2007)
A review was performed to determine the evidence base for scrub typhus indirect immunofluorescence assay (IFA) methodologies and the criteria for positive results. This review included a total of 109 publications, which comprised 123 eligible studies for analysis (14 publications included 2 substudies). There was considerable underreporting of the IFA methodology and seropositivity criteria used, with most studies using a defined cutoff titer rather than an increase in the titer in paired samples. The choice of positivity cutoff titer varied by country and purpose of the IFA test. This variation limits the comparability of seroprevalence rates between studies and, more seriously, raises questions about the appropriateness of the cutoffs for positive IFA results chosen for diagnosis of acute scrub typhus infection. We suggest that the diagnosis of scrub typhus using IFA should be based on a > or =4-fold increase in the titer in paired serum samples and should only be based on a single sample titer when there is an adequate local evidence base.